2022
DOI: 10.1002/cam4.5541
|View full text |Cite
|
Sign up to set email alerts
|

Poor association between dihydropyrimidine dehydrogenase (DPYD) genotype and fluoropyrimidine‐induced toxicity in an Asian population

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…A Japanese study investigated the incidence of DPD deficiency in 1362 Asian colon cancer patients who were enrolled in the JOIN 82 and ACHIEVE 83 adjuvant chemotherapy trials and suggested that the incidence of DPD deficiency for these patients was in the region of 0.6%, with no clear association observed between DPD deficiency and safety. 84 In addition, DPD deficiency was not detected by analysing DPD full-length RNA polymorphisms in peripheral blood mononuclear cells in 67 Taiwanese patients using multiplex nested reverse transcription-polymerase chain reaction (RT-PCR) and non-isotopic RNase cleavage assays (NIRCA). 85 DPD deficiency is also reported not to be common in Korea .…”
Section: Resultsmentioning
confidence: 99%
“…A Japanese study investigated the incidence of DPD deficiency in 1362 Asian colon cancer patients who were enrolled in the JOIN 82 and ACHIEVE 83 adjuvant chemotherapy trials and suggested that the incidence of DPD deficiency for these patients was in the region of 0.6%, with no clear association observed between DPD deficiency and safety. 84 In addition, DPD deficiency was not detected by analysing DPD full-length RNA polymorphisms in peripheral blood mononuclear cells in 67 Taiwanese patients using multiplex nested reverse transcription-polymerase chain reaction (RT-PCR) and non-isotopic RNase cleavage assays (NIRCA). 85 DPD deficiency is also reported not to be common in Korea .…”
Section: Resultsmentioning
confidence: 99%
“…To improve sensitivity, DPYD gene is currently under intense study for the identification of additional, population-specific, clinically relevant variants, rare mutations, and/or copy number variations ( Palles et al, 2021 ; De Luca et al, 2022 ; De Mattia et al, 2022 ; Kanai et al, 2022 ; Wigle et al, 2023 ). Indeed, results from a large scale genetic analysis in patients from the QUASAR2 clinical trial revealed three, additional to the CPIC-recommended, variants, namely, rs12132152, rs12022243, and p.Ala551Thr, that were associated with CAP-toxicity ( Rosmarin et al, 2015 ).…”
Section: Fluoropyrimidine Pharmacogenomicsmentioning
confidence: 99%
“…Whether the association of CES1 with FP-response is limited in non-Asian populations needs to be further investigated. Following the example of DPYD for which it has been reported that the registered CPIC variations have only a minor role in FP-related toxicity in an Asian population ( Kanai et al, 2022 ), we propose that CES1 could be initially incorporated in a polygenic FP dosing algorithm for other ancestries until firm conclusions are drawn on its potential effect on FP response in Asian populations. It appears that multiple CES1 variants should be considered as predictive factors to CAP-induced HFS.…”
Section: Fluoropyrimidine Pharmacogenomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that there are inter-ethnic differences in DPYD variant frequency. In fact, several studies have reported the absence of the European DPYD variants in populations from East and Southern Africa, namely Somalia, Kenya 42 and Zimbabwe 43 , and East Asia including China 44 and Japan [45][46][47][48] . In addition, variants that are not present in Europeans can have a profound impact in non-European populations, and vice versa 49 .…”
Section: Introductionmentioning
confidence: 99%